2016
DOI: 10.1177/0954411916650220
|View full text |Cite
|
Sign up to set email alerts
|

An insight into elasticity analysis of common carotid artery using ultrasonography

Abstract: Elastance is a distinguished marker in diagnosing various arterial diseases as studies have reported carotid artery-related diseases linked with stiffness index (β) values greater than 5. This study was to estimate elasticity of common carotid artery by measuring the diameter during systolic and diastolic phases using pixel tracing of successive frames and blood pressure. The B-mode ultrasonography video containing arterial wall motion was captured and fragmented into image frames. Each pixel on the greyscale … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Simplified rigid and compliant artery models of healthy CCAs were compared using PIV. The results demonstrated a significantly overestimated WSS in the rigid model 42 . Therefore, these studies emphasize the importance of vascular models with physiological compliance for realistic fluid dynamic investigations and implant characterization 41 .…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Simplified rigid and compliant artery models of healthy CCAs were compared using PIV. The results demonstrated a significantly overestimated WSS in the rigid model 42 . Therefore, these studies emphasize the importance of vascular models with physiological compliance for realistic fluid dynamic investigations and implant characterization 41 .…”
Section: Discussionmentioning
confidence: 82%
“…Ebrahimi et al reported the elastic modulus of actual cerebral arteries to range between 0.2 and 0.6 MPa in the physiological pressure range, depending on the microstructure of the vessel wall at various anatomical locations 29 . The elastic modulus of CCA in 19 patients was obtained by measuring the diameter during the systolic and diastolic phases using pixel tracing of successive frames and blood pressure in B-mode ultrasound, amounting to as 0.453 ± 0.099 MPa 42 . In our study, the elastic modulus was 0.31 ± 0.008 MPa and 0.29 ± 0.007 MPa for PVA-H and silicone, respectively, and thus lying in the lower range presented in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Creating a cross-sectional image of tissues using ultrasonic waves has become very common in modern medicine, due to being less expensive and risky as opposed to common imaging methods [1]. The imaging resolution of ultrasonic imaging increases with increasing working frequency of the US probe, so HF US imaging has become a new and valuable tool in applications such as skin imaging [2][3][4], eye imaging [1,5], intravascular imaging [6][7][8][9], Carotid artery imaging and elastography [10,11] and small animal imaging [12,13].…”
Section: Introductionmentioning
confidence: 99%